Students’ and Lecturers’ Perspectives of Integrated Course (IC) - Riza Weganofa; Fitri Anggraini Hariyanto (Jurnal Inspirasi Pendidikan, 2015)
Richards (2001:209) mentioned that many things can be done to create a good teaching- learning process, but it is the teachers that determine the success of teaching. Thus, the success teaching-learning process in S-1 degree becomes one of the foundations of national education. Integrated Course (IC) is one of compulsory course in English Department curriculum of University of Kanjuruhan Malang in the first semester. This course is aimed to improve students’ fluency in intermediate and pre-intermediate level. The contribution of this research is investigating of lecturers’ and students’ perspective about the implementation of IC along with the constraints of the course. Both lecturers and students viewed positively this course although listening got the lowest score from students’ perspective. Difficulties mostly faced by lecturers, including time constraint, various students’ levels of proficiency, and the books. Keywords: Students Perspective, Lecturers Perspective, Integrated Course